List of individuals enquired into - Cornish, F.
1902-01-01 1902 1900s 2 pages Dear Sir I have not quite finished the enquiries but hope to do so tomorrow, are these inquiries full enough for the purpose. Yours Faithfully F. Cornish C.H. Loch. Esq. From F. Cornish Re Various 1 Jan 1902 Ackd 1 Ansd 1 378/IMSW/A/1/6/8